Optimalisasi Sistem Teknologi Hybrid Pada Rancangan PV-Grid-Baterai Untuk Kebutuhan Skala Rumah Tangga - Syah Rinal Efendi; Arya Chandra Buana Lubis; Habib Satria; Indra Hermawan (Program Studi Teknik Elektro Fakultas Teknik Universitas Islam 45 Bekasi, 2022)
The use of electricity that has covered every area of ​​the earth is a valid fact. This makes electricity a primary need that must be continuously provided to meet the needs of the community. Based on these known facts, as much as 50% of this electricity user is in the form of a household scale. Therefore, a research was conducted on the analysis of the technology system conversion in the PV-grid-battery design at a household scale. This study aims to determine the level of technology conversion in the pv-grid-battery design at a household scale so that electric customers can utilize solar panel technology more optimally and well. The method used in this activity is to use a direct observation and data collection system. Based on the results obtained, it can be concluded that the use of solar panels with a capacity of 120 Wp x 2 can help in backing up loads on a household scale. The household load power which is the parameter in this research activity is 450 VA (based on the power of the household kWhmeter).